2020
DOI: 10.4236/jssm.2020.134043
|View full text |Cite
|
Sign up to set email alerts
|

Study on Knowledge Sharing Behavior of Users in Social Q&A Community

Abstract: Social Q&A community provides a new way for users to acquire, exchange and share information, so it is of great significance to study user's knowledge sharing behavior in social Q&A community. Based on the theory of social exchange, this paper takes Zhihu community as the research object, analyzes the factors that affect user's knowledge sharing behavior in the social Q&A community, and conducts quantitative research through negative binomial regression. The results show that in Zhihu community, self-display, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…In the study of users' knowledge-sharing behavior in the Zhihu social question-and-answer community, Gao et al ( 15 ) argued that in the Zhihu community, self-display, user recognition, social learning, and other dimensions have a positive and significant effect on users’ knowledge-sharing behavior. These results align with the present study's findings that the respondents' participation is affected by the components of motivations (personal and social).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of users' knowledge-sharing behavior in the Zhihu social question-and-answer community, Gao et al ( 15 ) argued that in the Zhihu community, self-display, user recognition, social learning, and other dimensions have a positive and significant effect on users’ knowledge-sharing behavior. These results align with the present study's findings that the respondents' participation is affected by the components of motivations (personal and social).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study of user knowledge sharing behavior in SQA community (based on Zhihu’s social exchange theory) showed that in Zhihu community, self-display, user recognition and recreational learning have significant positive effects on user knowledge sharing behavior. In other words, individuals with more detailed personal information had a greater desire for self-display ( 15 ).…”
Section: Introductionmentioning
confidence: 99%